Media Papan Huruf Terhadap Hasil Belajar SLB C Karya Tulus - Pinem, Irmina; Situmorang, Kresentia Kamilia; Sitompul, Nursani Gracia; Panjaitan, Hanna Florida; Hutajulu, Yohani; Sinurat, Daniyanti; Berutu, Ira Seviana; Siburian, Enzel Ulina (Lumbung Pare Cendekia, 2024)
The application of letter board media can improve the ability to recognize letters in children in SLB-C. The ability to recognize letters is an important development in children that must be developed from an early age. The ability to recognize letters in question is saying letters, showing letters, connecting letters with pictures. In this observation, the observer uses a direct observation method focused on the interaction between the teacher and students as well as the teaching methods used in the classroom. Based on the results of observations, improving the ability to recognize letters in children at SLB C Karyasincere through the application of letter board media. This can be done by the teacher introducing the letter board media to the children, directly practicing the activities that will be carried out, using the letter board media in turns, the teacher asking the children to name various letters, and combining the letters into one word. The ability to recognize children's letters after using this media shows increased results.